Nonlinear Pricing and the Utility Possibility Set - Tommy Andersson (Lund University, School of Economics and Management, Department of Economics, 2005)
We consider nonlinear pricing policies that are designed by a social welfare maximizer who operates under a non-negative profit requirement. In our two-type economy, we characterize the set of all feasible nonlinear pricing policies and the frontier of the utility possibility set. Our results provide a link between distortion in consumption and individual, as well as, social welfare.
Keywords: D42; D82; 330; Nonlinear Pricing; Budget-Balance; Welfare